The Soul of American in time of war, representative sermons by fifteen Unitarian ministers (The Beacon press, 1918)
The things that cannot be shaken, by F.G. Peabody.--A definite aim and an undaunted will, by H. N. Brown.--The spirit that makes men free, by S.A. Eliot.--The defence of out heritage, by J. D. Reid.--The immediate duty, by S. M, Crothers.--The law of sacrifice for men and nations, by W.L. Sullivan.--Angles in the wilderness, by P.R. Frothingham.--The willing sacrifice, by R. P.Doremus.--Are we worth dying for? By J.H. Holmes.--Interpreting the times, by G.R. Dodson.--Relion in action, by A. M. Lord.--The creative prupose of the Lore of life, by W.G. Eliot.--The uses of faith in war time, by R. W. Boynton.--The bow in the cloud, by A. P. Record.--Peace on the earth, by J.C. Perkins.